Decision Making Among Adult Offenders and Non-Offenders, Delaware, 2014-2015 - Paternoster, Raymond ([Verlag nicht ermittelbar], 2023)
This study examined the relationship between social preference game behavior and offender status, while testing whether this relationship was attributed to genuine prosocial preferences or confounded by individual differences in future orientation, sensation seeking, and risk-taking. The research team administered a hypothetical crime scenario (assault), which allowed for the experimental manipulation of certain key situational and contextual characteristics (e.g., rewards, peers) and framing considerations. The scenarios were crafted to be realistic for both the offender and non-offender respondents. The research team collected specific measures of parameters of the offender utility function, including measures of risk preferences, items that measure their discount rate and preferences for immediate vs. delayed rewards and costs, the magnitude of their motivation or craving for crime, and their decision-making style (intuitive vs. cognitive). Additionally, this study includes other measures of offender preferences, including fairness and social considerations, as well as related cognitive and behavioral measures (e.g., sensation-seeking, impulsivity).